Sustainability Status of Gillnet Capture Fisheries Based on Economic, Ecological, Technological, Institutional, and Social Aspects in Panipahan Pasir Limau Kapas Sub-District Rokan Hilir District - Simanjuntak, Jeremi Nichola; Brown, Arthur; Zain, Jonny (Science, Technology, and Education Care, 2025)
Rokan Hilir Regency, particularly Pasir Limau Kapas District, has significant potential for capture fisheries. However, ecosystem sustainability depends on high-value fish resources such as senangin and mackerel. Therefore, a sustainable study of fisheries management is needed based on ecological, socioeconomic, community, and institutional dimensions to ensure the sustainable use of fish resources. This research evaluates the sustainability status of gill net capture fisheries in Panipahan, Pasir Limau Kapas District, Rokan Hilir Regency, based on five dimensions: economic, ecological, technological, institutional, and social. The analysis method used is Rapid Appraisal for Fisheries (RAPFISH) with a Multidimensional Scaling (MDS) approach. The results show that the institutional dimension had the highest sustainability index at 92.08%, classified as